Dampak Kebijakan Batas Maksimal Potongan Aplikasi Sebesar 8% terhadap Kompensasi Pengemudi Ojek Online - Sendy Marcello Edy Putra; Ismatul Eka Novita Sari; Fina Karima; Rafika Meilia Sari (Indo Publishing, 2026)
This study aimed to analyze the impact of the maximum 8% application fee deduction policy on the compensation of online ojek drivers from a Human Resource Management perspective. The study used a qualitative approach with a library research method by reviewing scientific journals, government regulations, news articles, and previous studies related to the compensation system of online ojek drivers. The results showed that fare systems, bonuses, incentives, and application fee deductions significantly affected drivers’ income levels, work motivation, productivity, and welfare. Before the policy was implemented, application deductions reaching 20% were considered to reduce drivers’ net income, which negatively affected job satisfaction and work motivation. After the implementation of the maximum 8% deduction policy, drivers were expected to receive higher net income, which could improve welfare, job satisfaction, and work productivity. The study concluded that the policy of limiting application deductions represented a form of government intervention capable of creating a more proportional and equitable compensation system for online ojek drivers in the digital economy.